2018
DOI: 10.15345/iojes.2018.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Mathematics and Science Self-Efficacy Resources as the Predictor of Academic Success

Abstract: The basic aim of the study was to determine the power of mathematics and science self-efficacy resources as the predictors of academic success. The relational scanning model was used in the study, and the study was conducted with 492 students who were studying at sixth and seventh grades of a state school. The mathematics and science self-efficacy resources scales were used as the data collection tool. In addition, the school reports of the semester before the study was conducted were used to determine the aca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 43 publications
(112 reference statements)
3
15
0
Order By: Relevance
“…It can be concluded that sources of self-efficacy have a direct impact on mathematics achievement. In addition, there are research on the direct effect of sources of self-efficacy on academic performance in the literature (Keşan and Kaya, 2018;Özcan and Kültür, 2019). These findings support the findings of this study.…”
Section: Discussionmentioning
confidence: 99%
“…It can be concluded that sources of self-efficacy have a direct impact on mathematics achievement. In addition, there are research on the direct effect of sources of self-efficacy on academic performance in the literature (Keşan and Kaya, 2018;Özcan and Kültür, 2019). These findings support the findings of this study.…”
Section: Discussionmentioning
confidence: 99%
“…The results related to the covariate variable, mathematics achievement, showed that mathematics achievement had a significant effect on the four SMS: mastery experience, vicarious experience, social persuasions, and physiological state. Some studies showed that self-efficacy affected mathematics achievement (Bonne & Johnston, 2016;Grigget al, 2018;Masitoh & Fitriyani, 2018;Schober et al, 2018;Tossavainen et al, 2019;Watson, 2015;Zimmerman et al, 2011) and that SMS affected academic achievement (Arslan, 2013;Choy, 2013;Kesan & Kaya, 2018;Ozcan & Kontas, 2020). This study indicated that mathematics achievement influenced SMS, and it is consistent with studies showing that academic achievement affects self-efficacy (Hwang et al, 2016;Talsma et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…O'brien et al (1999) reported a low number of minorities in science and engineering due to deficits in self-efficacy or self-perceived skills in mathematics. Mathematics achievement is related not only to self-efficacy beliefs (Masitoh & Fitriyani, 2018;Watson, 2015;Zimmerman et al, 2011) but also to SMS beliefs (Arslan, 2013;Choy, 2013;Kesan & Kaya, 2018;Ozcan & Kontas, 2020;Ozcan & Kultur, 2019). On the contrary, recent studies have examined the possibility of the interplay of self-efficacy and academic achievement.…”
Section: Self-efficacy and Mathematics Achievementmentioning
confidence: 99%
“…However, there were significant relations between the self-efficacy of Mathematics and Science to their academic performance. The relation between the self-efficacy of these two subjects is correlated with their academic performance [23].…”
Section: Relationship Between Self-efficacy and Mathematics Performancementioning
confidence: 99%